Gene expression changes in leaves of Citrus sinensis (L.) Osbeck infected by Citrus tristeza virus. Issue 5 (2nd September 2016) - Cheng, Chunzhen; Zhang, Yongyan; Zhong, Yun; Yang, Jiawei; Yan, Shutang
ABSTRACT: Transcriptional changes between Citrus tristeza virus (CTV) inoculated- and mock inoculated- sweet orange 'Jincheng' ( Citrus sinensis Osbeck cv. 'Jincheng') leaves were compared using microarrays. A total of 2400 differentially expressed genes (DEGs, fold change ≥ 2), 1557 (64.85%) up-regulated and 843 (35.15%) down-regulated, were obtained. Data mining revealed that CTV infection enhanced the transcription of genes involved in cell wall metabolism, plant defense, and material transport while it decreased the expression of protein synthesis and cytokinin metabolism-related genes. CTV infection strongly affected pathways involved in light reaction, starch and sucrose metabolism, lipid metabolism, and hormone metabolism. Secondary metabolism pathways including terpenoids, phenylpropanoids, flavonoids and alkaloid metabolism were also greatly influenced. Notably, several gibberellin (GA)-regulated genes were significantly induced by CTV. Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to confirm the expression changes of 13 DEGs detected by microarray analysis. Our data described the early molecular changes of sweet orange in response to CTV infection and should provide informative suggestions for transgene selection of citrus genetic breeding.